Measuring expectations : revitalization of the United Nations general assembly. - Sammy Kanadi. (2010)
The General Assembly is the largest organ of the United Nations and is the manifestation of the organization's principles of democracy and universality. The Charter of the United Nations gives the General Assembly precedence over other principal organs, yet ironically it has always lived under the shadow of the Security Council. Over the years it has been marginalized to the extent that even proposals for its revitalization have been of little concern to the world community at large. Nevertheless the General Assembly is a creation without substitution. Its universality is unrivaled by any other international organization. Its capacity for acting as the world's foremost deliberative body is highly prized by states which believe that military and economic might are not the only capitals required to exercise international relations. This dissertation is therefore an attempt to assess revitalization of the United Nations General Assembly. It explores the General Assembly process and seeks to explain why it works the way it does. It discusses the body's incompetence as well as its potentialities. It subsequently examines various revitalization proposals, analyzes their advantages and viability, and - while finding many obstacles to change -identifies possible paths to revitalization.